PEMANFAATAN LIMBAH SAMPAH ORGANIK RUMAH TANGGA MELALUI MEDIA LUBANG RESAPAN BIOPORI DI DESA GUNUNG MALANG, KABUPATEN LOMBOK TIMUR - Irfani, Adra Mihra; Ningsih, Surya; Apryany, Ressy Eny; Ramdoni, Ramdoni; Kinanthi, Nimas Sekararum; Ramdan, M.; Islami, Muhammad Mafaza; Fadilah, Nabila; Awalyia, Azizah; Yazid , M. Gibran Asher (Universitas Mataram, 2024)
Waste is one of the problems that are found in many countries throughout the country. Waste is waste produced by the activities of living things and then thrown away without waste management, causing accumulation. The accumulation of garbage is the result of low public awareness regarding the importance of waste processing activities, especially household waste which is found in every house in an area. The amount and type of waste continues to increase, This can be seen from data from the National Waste Management Information System (SIPSN) in 2024 which notes that unmanaged waste reaches 35.96% equivalent to 11,605,262.32 tons/year, based on the source household waste reaches 49.6% of other waste. The problem is related to the amount of waste that is not processed properly, causing the environment to be dirty in Gunung Malang village. The pile of household waste consisting of organic and inorganic waste is due to the limited landfill (TPA) and waste transportation fleets that enter the Gunung Malang village area, in addition to the lack of public awareness related to waste sorting and management is the cause of the lack of cleanliness and environmental health. The solution obtained is to conduct education on waste sorting and the use of organic waste by using the biopore infiltration hole method as an organic waste disposal site. Providing material related to the benefits of biopore infiltration holes by DLHK and planting at several points. Biopore infiltration holes function as water catchments and organic waste reservoirs that have benefits as compost.